ASSESSING FACTORS AFFECTING the REPAYMENT RATE OF MICROFINANCE INSTITUTIONS: A Case Study of Village Credit Institutions of Gianyar, Bali - Arsyad, Lincolin (Gadjah Mada International Journal of Business, 2006)
This paper attempts to assess the influence of several factors on the repayment rate of the Village Credit Institutions (Lembaga Perkreditan Desa or simply LPDs) in Gianyar district in Bali. Using a quantitative approach (logistic model) the findings of this study indicate that the Balinese social custom, including social values, norms, and sanctions (informal institutions) have an influence on sustaining the high repayment rate of the LPDs. This finding conforms to the some previous studies using institutional approach that reveal the high repayment rate of the LPDs in Gianyar district is influenced by their institutional arrangement that based on custom regulation which includes social norms, sanctions, and involvement of custom village leader in screening process and contractual enforcement of loan (informal institutions), by regulations set up by the Central Bank (formal institutions), and by the mechanism of collecting loan repayments applied by the LPDs management.